Philippines Lessons Learned from Yolanda : An Assessment of the Post-Yolanda Short- and Medium-Term Recovery and Rehabilitation Interventions of the Government - World Bank (Washington, DC, 2017)
The Philippines is increasingly exposed and vulnerable to natural hazards, which undermines poverty reduction and long-term growth. Typhoon Yolanda (Haiyan), which struck the Philippines in 2013, is considered the strongest typhoon ever to make landfall. Typhoon Yolanda has caused over 6,300 reported fatalities and an additional 2.3 million people were estimated to have fallen below the poverty line. The total damage and loss was estimated at PHP 571.1 billion (USD 12.9 billion) hampering economic growth by about 0.9 % in 2013, and another 0.3 % in 2014. The event highlighted the following major issues on the side of government and all other non-government actors: coordination at all levels, aid transparency and accountability, systems and protocols for donations and assistance, conduct of post-disaster needs assessment, recovery planning, implementation, monitoring, and communications.